The influence of organizational culture on attitudes toward organizational change - Md Zabid, Abdul Rashid, Prof Dr; Murali , Sambasivan; Azmawani , Abdul Rahman (2004)
This study investigates the influence of organizational culture on attitudes toward organizational change in Malaysia. Based on the work of Goffee and Jones and Dunham et al., a structured questionnaire was developed and self-administered to 258 companies listed in the Federation of Malaysian Manufacturing directory. The results showed that there is an association between organizational culture and the affective, cognitive, and behavioral tendency of attitudes toward organizational change. The findings also showed that different types of organizational culture have different levels of acceptance of attitudes toward organizational change. This means that certain type of organizational culture could facilitate the acceptability of change, while other types of culture could not accept it. The implications of this research are also discussed. (Authors' abstract)